Leadership Style and Performance of Employees - Agarwal, Sugandha (Universitas Prasetiya Mulya, 2020)
Leadership is an important aspect as it usually enables the employees of the organizations to work efficiently and effectively. The current study assesses the relationship between leadership style(s) and the performance of employees working in the banking sector of the United Arab Emirates (UAE). This quantitative study is conducted with a sample of 200 employees from 5 different banking institutions of the UAE using simple random sampling techniques. SPSS version 21 was used to analyze the data. The results highlighted that democratic and transformational leadership have a significant positive relationship with the performance of employees with a p-value of 0.00, P<0.05. The Cronbach’s alpha was measured between the ranges of 0.7 to 0.8 which is an acceptable range. It is proven that democratic leadership and transformational leadership styles are significant for the banking sector which helps to achieve its goals and enhance the performance of employees.